2018
DOI: 10.1016/j.rmed.2018.07.009
|View full text |Cite
|
Sign up to set email alerts
|

Clinical characteristics and medication patterns in patients with COPD prior to initiation of triple therapy with ICS/LAMA/LABA: A retrospective study

Abstract: Overall, it appears that in this patient population, ICS/LAMA/LABA as triple therapy is being initiated after use of a bronchodilator and/or after an exacerbation event, in accordance with accepted treatment recommendations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
25
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(30 citation statements)
references
References 26 publications
5
25
0
Order By: Relevance
“…Earlier studies have shown that a history of exacerbations is predictive of the future risk of exacerbations, [36, 16, 17] which was observed in our study as well. We found that frequent exacerbators (≥2 exacerbations) continued to be exacerbators (≥1 exacerbations) in the subsequent follow-up.…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…Earlier studies have shown that a history of exacerbations is predictive of the future risk of exacerbations, [36, 16, 17] which was observed in our study as well. We found that frequent exacerbators (≥2 exacerbations) continued to be exacerbators (≥1 exacerbations) in the subsequent follow-up.…”
Section: Discussionsupporting
confidence: 89%
“…A previous study in COPD population without excluding patients with concurrent asthma from the UK had reported 20% of patients with eosinophil counts, of which approximately 65% had eosinophil count ≥150 cells/μL [3]. In another study, 20% of patients had eosinophil count ≥300 cells/μL and 11% had ≥400 cells/μL [6].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, other factors such as exposure to air pollutants, may increase oxidative stress and inflammation in the lungs and contribute to the susceptibility of development of COPD. 2 COPD encompasses two serious lung disease emphysema and chronic bronchitis (CB) which results in chronic airway inflammation and progressive loss of lung function, making it difficult to breathe normally. 3 COPD is a chronic, non-communicable disease which poses a continuous burden on health care infrastructure.…”
Section: Introductionmentioning
confidence: 99%
“…Current treatment guidelines recommend the use of triple therapy with an ICS/LAMA/LABA for patients currently on bronchodilators with continued persistent symptoms and/or at risk for future exacerbations. 2,6,7 Prescription pattern monitoring studies (PPMS) are drug utilization study which is a tool that mainly focuses on prescribing and administering of drugs. They promote appropriate use of monitored drugs and reduction of abuse or misuse of monitored drugs.…”
Section: Introductionmentioning
confidence: 99%